Utilization of Human Induced Pluripotent Stem Cells for Cardiac Repair - Fan, Chengming; Zhang, Eric; Joshi, Jyotsna; Yang, Jinfu; Zhang, Jianyi; Zhu, Wuqiang (Frontiers in Cell and Developmental Biology, 2020)
The paracrine effect, mediated by chemical signals that induce a physiological response on neighboring cells in the same tissue, is an important regenerative mechanism for stem cell-based therapy. Exosomes are cell-secreted nanovesicles (50–120 nm) of endosomal origin, and have been demonstrated to be a major contributor to the observed stem cell-mediated paracrine effect in the cardiac repair process. Following cardiac injury, exosomes deriving from exogenous stem cells have been shown to regulate cell apoptosis, proliferation, angiogenesis, and fibrosis in the infarcted heart. Exosomes also play a crucial role in the intercellular communication between donor and recipient cells. Human induced pluripotent stem cells (hiPSCs) are promising cell sources for autologous cell therapy in regenerative medicine. Here, we review recent advances in the field of progenitor-cell derived, exosome-based cardiac repair, with special emphasis on exosomes derived from hiPSCs.